IMPLEMENTASI MEKANISME PASAR MADINAH DALAM MENDORONG EKONOMI BERKELANJUTAN - Muhammad Syauqi Yunilhamri; Muhammad Adnan Azzaki (Faculty of Economics and Islamic Business, Sunan Drajat University, Lamongan, 2025)
This study examines the role of the Medina market mechanism in supporting the achievement of a sustainable economy. The Medina market, established by the Prophet Muhammad, provides a fair, transparent, and monopolistic market model, and prioritizes balance between economic, social, and environmental aspects. Through the principle of prohibition of usury, price control, and redistribution of wealth through zakat and alms, the Medina market not only ensures economic sustainability, but also creates social justice and solidarity between communities. The research method used is a literature study with a descriptive-analytical approach. This study concludes that the principles applied in the Medina market can be used as a reference in efforts to overcome social and economic inequality in the modern era. Furthermore, the zakat and alms system implemented at that time proved to be an effective instrument in reducing poverty and improving wealth distribution. In the context of today's global economy, the values contained in the Medina market mechanism can make a significant contribution to more inclusive and sustainable economic development. Therefore, the application of the Medina market principles in the future, by considering changes in the times and the needs of society, can lead to the achievement of sustainable development goals.